2019
DOI: 10.1177/016146811912101407
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Adolescent Social Media Use in a High School: Tweeting Teens in a Bell Schedule World

Abstract: This multilevel exploratory case study examined the intersection of adolescent social media use and administrators’ and teachers’ work in one Florida high school. Through a survey and activities with 48 high school students and interviews with 37 students and 18 administrators and teachers in a Florida high school, we explored the different ways that students and adults used social media both outside and in school. We found that students and adults engaged in active and intentional community building and infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The age range 13–18 was important to us because the purpose of this review is to understand what is known about the social media practices of adolescents ages 13–18, so we might further research to better support students and teachers in secondary education. We had to cut a substantial number of articles from both the education technology and literacy because the research included participants over 18 in their study (see literacy: Saal & Gómez, 2020; Tucker-Raymond et al, 2017; and educational technology: Moekotte et al, 2015; Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The age range 13–18 was important to us because the purpose of this review is to understand what is known about the social media practices of adolescents ages 13–18, so we might further research to better support students and teachers in secondary education. We had to cut a substantial number of articles from both the education technology and literacy because the research included participants over 18 in their study (see literacy: Saal & Gómez, 2020; Tucker-Raymond et al, 2017; and educational technology: Moekotte et al, 2015; Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We chose to investigate out of school environments specifically because the literacy practices of adolescents are different outside of school than in school (Hull & Schultz, 2001;Moje et al, 2004). Also, adolescents may use social media differently in school than out of school because school policy may limit the use of social media at school, and the non-academic use of social media, which is it most often used for, may be not be allowed at school (Rutledge et al, 2019).…”
Section: Stage 1: Identifying the Research Questionmentioning
confidence: 99%
“…Social media has the power to influence a teen's decision-making skills by connecting them to their peers [1]. This can especially impact health-risk behaviors like the use of alcohol and tobacco [25]. Teenagers are able to be connected to social media 24 hours a day and 7 days per week, allowing them constant exposure to carefully molded profiles that project perfected images [26].…”
Section: A Adolescent Identity Development and Social Mediamentioning
confidence: 99%
“…In general, there has been an observable increase in the use of digital media: while television and printed press as media are declining among adolescents, the use of new technologies (i.e., messaging, Internet usage, and online gaming) has remained constantly high in recent years and, in particular, there has been an increase in the use of social networking sites that, especially for girls, have become an integral part of the daily routine for a high number of teenagers [ 26 ]. Girls also tend to use technology for social networking sites in a more consistent way than boys—especially those that are mostly focused on sharing multimedia content (i.e., Instagram, Snapchat)—while boys seem to mostly be involved in online gaming platforms or communities focused on specific interests [ 27 ]. However, it was found that in both genders, social media sites are seen as an important resource to interact with friends, find new friendships or receive support and advice, and interact with the community, but also to study, acquire new skills, and create connections that might be useful for their future academic career [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Girls also tend to use technology for social networking sites in a more consistent way than boys—especially those that are mostly focused on sharing multimedia content (i.e., Instagram, Snapchat)—while boys seem to mostly be involved in online gaming platforms or communities focused on specific interests [ 27 ]. However, it was found that in both genders, social media sites are seen as an important resource to interact with friends, find new friendships or receive support and advice, and interact with the community, but also to study, acquire new skills, and create connections that might be useful for their future academic career [ 27 , 28 ]. Within this framework, the COVID-19 pandemic ended up facilitating a further increase in ICT use [ 29 ], and now many teenagers are even exhibiting behavior that is very close to technology-addiction behavior [ 30 ].…”
Section: Introductionmentioning
confidence: 99%